Non‐genetic and genetic rewiring underlie adaptation to hypomorphic alleles of an essential gene. (15th September 2021) - Targa, Altea; Larrimore, Katherine E; Wong, Cheng Kit; Chong, Yu Lin; Fung, Ronald; Lee, Joseph; Choi, Hyungwon; Rancati, Giulia
Abstract: Adaptive evolution to cellular stress is a process implicated in a wide range of biological and clinical phenomena. Two major routes of adaptation have been identified: non‐genetic changes, which allow expression of different phenotypes in novel environments, and genetic variation achieved by selection of fitter phenotypes. While these processes are broadly accepted, their temporal and epistatic features in the context of cellular evolution and emerging drug resistance are contentious. In this manuscript, we generated hypomorphic alleles of the essential nuclear pore complex (NPC) gene NUP58 . By dissecting early and long‐term mechanisms of adaptation in independent clones, we observed that early physiological adaptation correlated with transcriptome rewiring and upregulation of genes known to interact with the NPC; long‐term adaptation and fitness recovery instead occurred via focal amplification of NUP58 and restoration of mutant protein expression. These data support the concept that early phenotypic plasticity allows later acquisition of genetic adaptations to a specific impairment. We propose this approach as a genetic model to mimic targeted drug therapy in human cells and to dissect mechanisms of adaptation. Synopsis: Two major routes of adaptation are known‐ non‐genetic changes and genetic variation, yet their temporal and epistatic features in the context of cellular evolution and emerging drug resistance are not fully understood. Here, an approach for adaptive evolution in response to the functional impairment of the essential gene NUP58 in human cells shows that early adaptation occurs by phenotypic plasticity and rewiring of the transcriptional network, while late adaptation and fitness gain occurs by genetic change. Early cellular adaptation to NUP58 impairment is driven by upregulation of karyopherins, a class of NUP58 functionally related proteins. Late adaptation is driven by mutant NUP58 focal amplification. These results support the concept that early non‐genetic changes allow later acquisition of genetic adaptations to a specific impairment. Generation of hypomorphic alleles and dissection of the adaptation mechanisms to restore fitness can be a novel in vitro model to mimic targeted drug therapy and to identify drug resistance mechanisms. Abstract : Generation of hypomorphic alleles of NUP58 in human cells using CRISPR‐Cas9 provides a proof‐of‐principle demonstration that early non‐genetic changes allow later acquisition of genetic adaptations to a specific impairment.